“#I-Am-Engaged”: Conceptualization and First Implementation of a Multi-Actor Participatory, Co-designed Social Media Campaign to Raise Italians Citizens’ Engagement in Preventing the Spread of COVID-19 Virus - Graffigna, Guendalina; Bosio, Caterina; Savarese, Mariarosaria; Barello, Marina; Barello, Serena (Frontiers in Psychology, 2020)
COVID19 pandemic forced health authorities around the world to introduce public health measures to contain the risks of contagion. This greatly impacted on citizens’ quality of life, often raising concerns and reactance. To promote sensitizing campaigns able to sustain citizens’ behavioral change and adherence to preventive measure is still nowadays urgent. Based on the theoretical framework of the Patient Health Engagement Model and on a participatory co-design process, a social media campaign aimed at improving citizens’ health engagement towards behavioral change for preventing the COVID19 spread was promoted in Italy in the early months of the pandemic. In this paper we describe the methodological process adopted, the characteristics of the campaign and the first results achieved. The discussion of this grounded up and citizen-centred approach to social campaign development highlights the key learning for engaging citizens and supporting their participation in the co-production of educational interventions for behavioral change towards preventive actions.